FILIAL PIETY THROUGH JING SI APHORISMS: PARENTAL INSIGHTS IN TZU CHI DA AI KINDERGARTEN MALAYSIA - Chua, Soo Sien; Kuek, Florence; Ching , Thing Ho (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
In an era of accelerating modernization, conveying filial traditional familial values among younger generations brings challenges in Malaysia’s diverse society. Jing Si Aphorisms’ teachings, drawn from Tzu Chi’s humanistic education, serve as a culturally embedded moral guide in shaping children’s behavior, emphasizing respect, gratitude, and ethical behavior in daily life. This study explores the integration and internalization of Jing Si Aphorisms’ teachings on filial piety to young children from parents’ perspectives in Tzu Chi Da Ai Kindergarten, Malaysia. Using a qualitative approach, semi-structured interviews and a Nominal Group Technique (NGT) session were conducted to explore the integration of Jing Si Aphorisms teaching and consensus on children’s filial attitudes. Eight parents with children aged 5 and 6 were selected through purposive sampling. Interview findings concluded filial piety inculcation through intentional valuesteaching through daily routines, Jing Si Aphorisms methods, home-school collaboration reinforcement, and value-based activities. For NGT results, the concluded themes on Jing Si Aphorism behavioral influence include recital of the Jing Si Aphorism, reflection, empathy, verbal and expression of gratitude, practicing self-living skills, helping with household chores, and abiding by family daily rules of conduct. Notably, findings reveal that consistently integrating Jing Si Aphorisms teaching into daily activities and fostering continuity between home and school moral education cultivates positive filial piety behaviors in children and parent-child relationships. Filial piety behavior, which is most influenced by the teaching of Jing Si Aphorisms, is the verbal expression of gratitude. As such, the findings highlight the significance of culturally contextualized Jing Si Aphorisms in shaping early character development. Therefore, early exposure to value-based approaches in early childhood settings is effectively nurtured through aphorism-based teaching. Similarly, collaborative efforts between school and home promote holistic moral development effectively. Thus, this study contributes to the discourse on value-based education, providing empirical evidence on how culturally rooted Jing Si Aphorisms values instill moral values in preschool-aged children.